1991
DOI: 10.1095/biolreprod44.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Whole-Body Androgen Content in Rats on Fetal Days 18 and 19 Without Evidence that Androgen Passes from Males to Females1

Abstract: The whole-body content of androgen (testosterone + 5 alpha-dihydrotestosterone) was significantly higher on Fetal Days 18 and 19 in male than in female rats; androgen content was equivalent in the two sexes at other fetal ages, including Days 16, 17, 20, and 21, and prior to parturition on Fetal Day 22. These results partially corroborate previous data of Weisz and Ward (Endocrinology 1980; 106:306-316), who measured testosterone in pooled plasma from rat fetuses and suggest that androgens contribute to mascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…Quantitative examination of androgens in fetal rats shows that males and females have similar androgen content during much of gestation (Baum et al 1991;Weisz and Ward 1980). However, concentrations of androgens in males increase significantly late in gestation (Baum et al 1991;Houtsmuller et al 1995;vom Saal and Bronson 1980;Weisz and Ward 1980), reaching a peak around the critical developmental window of GDs 18-19 (Baum et al 1991).…”
Section: Natural Variation In Androgen Concentrations During Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative examination of androgens in fetal rats shows that males and females have similar androgen content during much of gestation (Baum et al 1991;Weisz and Ward 1980). However, concentrations of androgens in males increase significantly late in gestation (Baum et al 1991;Houtsmuller et al 1995;vom Saal and Bronson 1980;Weisz and Ward 1980), reaching a peak around the critical developmental window of GDs 18-19 (Baum et al 1991).…”
Section: Natural Variation In Androgen Concentrations During Developmentmentioning
confidence: 99%
“…Quantitative examination of androgens in fetal rats shows that males and females have similar androgen content during much of gestation (Baum et al 1991;Weisz and Ward 1980). However, concentrations of androgens in males increase significantly late in gestation (Baum et al 1991;Houtsmuller et al 1995;vom Saal and Bronson 1980;Weisz and Ward 1980), reaching a peak around the critical developmental window of GDs 18-19 (Baum et al 1991). Several studies have suggested that this brief exposure to elevated androgens late in gestation sensitizes the developing male to androgen exposure during the neonatal period (Baum et al 1990;Hoepfner and Ward 1988;Tobet and Baum 1987).…”
Section: Natural Variation In Androgen Concentrations During Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we cannot determine from the present data whether or not sexual differentiation of forebrain ARs occurs and, if it happens, whether it takes place pre-or neonatally under the influence of androgens or estrogens. 9,10,43,45,51,53 Future studies should address these questions.…”
Section: Androgen Receptor Immunoreactivitymentioning
confidence: 99%
“…Both testosterone and estradiol are necessary for normal sexual differentiation of the male brain [98]. In developing females, although it has been proposed that the fetal ovary is relatively quiescent compared to the male testis, it is important to note that androgens and estrogens are measurable in the late embryonic period in female rats [13,70]. However, sexual differentiation of the female and male brain still differs due in part to alpha-fetoprotein, which protects the brain from effects of maternal estrogens [10,42].…”
Section: Introduction To Development Of Reproductive Neuroendocrine Cmentioning
confidence: 99%